2021
DOI: 10.3389/fnbeh.2021.736778
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Recognition Memory: Differential Brain Strategic Activation According to Sex

Abstract: Human spatial memory research has significantly progressed since the development of computerized tasks, with many studies examining sex-related performances. However, few studies explore the underlying electrophysiological correlates according to sex. In this study event-related potentials were compared between male and female participants during the performance of an allocentric spatial recognition task. Twenty-nine university students took part in the research. Results showed that while general performance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 88 publications
(138 reference statements)
0
8
0
Order By: Relevance
“…This sample size was similar to that in a previous study investigating contrast sensitivity in MDD patients (Bubl et al, 2009). Moreover, using G*Power (Version 3.1; Faul et al, 2007), we conducted a post‐host power analysis (Castillo et al, 2021; Civile et al, 2018; Thakral et al, 2021) for the main effect of group identified in the contrast discrimination task. The post‐host power analysis was performed based upon effect size (the η 2 p of .20 calculated in the current study gave an effect size of .50), alpha level (.05) and total sample size (i.e., N = 63).…”
Section: Methodsmentioning
confidence: 99%
“…This sample size was similar to that in a previous study investigating contrast sensitivity in MDD patients (Bubl et al, 2009). Moreover, using G*Power (Version 3.1; Faul et al, 2007), we conducted a post‐host power analysis (Castillo et al, 2021; Civile et al, 2018; Thakral et al, 2021) for the main effect of group identified in the contrast discrimination task. The post‐host power analysis was performed based upon effect size (the η 2 p of .20 calculated in the current study gave an effect size of .50), alpha level (.05) and total sample size (i.e., N = 63).…”
Section: Methodsmentioning
confidence: 99%
“…Also, as prior studies reported 20 , clockwise superiority could also be present in event-related potentials (ERP) measures, and hemispheric lateralization could also be relevant, resulting in differential activations depending on the rotation type 21 . A recent study also outlines differential activations according to sex factor in spatial recognition for complex stimuli 90 . Thus, to properly disclose if clockwise superiority is consistent for complex stimuli, and how it interacts with sex and age, subsequent studies integrating electroencephalography (EEG) measures need to be performed to extend our findings further beyond.…”
Section: Discussionmentioning
confidence: 97%
“…After providing informed consent, participants completed the pre-screening interview (see exclusion criteria in the Participants section) and the Corsi test ( Spinnler and Tognoni, 1987 ). Only participants with a visuospatial memory span of 7 ± 2 ( Miller, 1994 ) were invited to complete the task; for convergent validity, the Circle Task ( Castillo et al, 2021 ) was also used to assess visuospatial working memory capabilities. Finally, the Repeatable Battery for the Assessment of Neuropsychological Status battery (RBANS) ( Randolph et al, 1998 ) was used as a general assessment of cognitive abilities.…”
Section: Methodsmentioning
confidence: 99%
“…If Block was not statistically significant as a main effect or in interaction with other factors, data were averaged across blocks and analyzed with a 2 × 4 mixed-factorial ANOVA with Sex (2: male, female) as the between-subject factor and Temporal Condition (4: FF, FV, VF, VV) as the repeated measure factor (see Supplementary material for additional analyses on data distribution). For convergent validity, multivariate regression was used to assess whether accuracy and response time at the Time Squares Sequences predicted the K-INDEX, which identifies the number of items present in working memory using false alarms and hit rates, and RT at Circle Task ( Castillo et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%